Streamlining Mortgage Workflows with Automation: A Technical Implementation Guide - Suketu Pramod Gaglani, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Mortgage industry automation represents a transformative shift in lending operations, offering solutions to longstanding challenges in processing efficiency and operational costs. This article presents a comprehensive framework for implementing automation technologies, including robotic process automation (RPA), artificial intelligence, and machine learning, within existing mortgage workflows. Through detailed analysis of integration methodologies, technical architecture requirements, and performance optimization strategies, this article provides practical guidance for mortgage professionals seeking to modernize their operations. The discussion encompasses critical aspects of successful automation implementation, from initial assessment and strategic planning to risk mitigation and staff training. Special attention is given to maintaining compliance standards and ensuring human oversight in crucial decision-making processes. By addressing both technical and operational considerations, this article serves as a roadmap for lending institutions aiming to achieve operational excellence through automation while preserving the essential human elements of mortgage processing.
Keywords: Mortgage Automation; Digital Transformation; Workflow Optimization; Process Integration; Financial Technology